Notes on Phlebotomine sand flies of Michoacán, Mexico, with a key - Ibáñez-Bernal, Sergio; Ibarra Juárez, Luis Arturo (Instituto de Ecología, A.C., 2016)
Four species of phlebotomine sand flies were collected in the Municipality of Sahuayo, on the High Plateau of Michoacán, representing the first records of phlebotomine sand flies in this region. Two of them, Micropygomyia (Coquillettimyia) vindicator (Dampf) and Psathyromyia (Forattiniella) texana (Dampf), are new records for Michoacán. A total of ten phlebotomine species are now known to occur in this state, and we present a key for their identification.